Chromosomal and subchromosomal anomalies associated to small for gestational age fetuses with no additional structural anomalies. (3rd December 2017) - Peng, Ruan; Zhou, Yi; Xie, Hong‐Ning; Lin, Mei‐Fang; Zheng, Ju
Abstract : What's already known about this topic? Published studies have shown a 6.8 to 11.4% incremental yield of chromosomal abnormalities over karyotyping in SGA cases combined with structural anomalies or nonstructural anomalies. What does this study add? Our study showed that chromosomal and subchromosomal anomalies occurred in 7.8% (10/128) SGA fetuses with no additional structural anomalies, among which 9 cases could be identified with CMA. Chromosomal and subchromosomal anomalies occurred significantly higher in cases with oligohydraminos and in early onset cases. Abstract: Objectives: To assess the chromosomal and subchromosomal anomalies in small for gestational age (SGA) fetuses with no additional structural anomalies and their clinical outcomes. Methods: This study retrospectively reviewed the 128 SGA fetuses with no additional anomalies and underwent genetic testing with karyotyping and chromosomal microarray analysis (CMA). Stratified analysis was performed according to the existence of maternal risk factors for SGA (yes or no), gestational age at onset (before or after 32 weeks), presence of oligohydraminos (yes or no), and umbilical artery Doppler flow (normal or abnormal). Results: Chromosomal anomalies were identified in 6 (4.7%) SGA fetuses and pathogenic subchromosomal anomalies in 4 (3.1%) by microarray analysis. Chromosomal and subchromosomal anomalies were more frequently observed in cases with oligohydraminos ( P = .017) and with early‐onset SGA ( P = .042). No differences were observed in relation to the existence of maternal risk factors and abnormal umbilical artery Doppler flow. Overall survival rate was 75.0% with different rates in the early and the late onset group ( P < .001). Conclusions: There is a 3.3% incremental yield of subchromosomal anomalies in CMA above karyotyping in SGA fetuses. Chromosomal microarray analysis is recommended in SGA fetuses with no additional structural anomalies, especially coexisting with oligohydraminos and being early onset.